2019
DOI: 10.1590/s1678-3921.pab2019.v54.00215
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal evolution of imidazolinone-resitant red rice in 'Clearfield' rice cultivations

Abstract: The objective of this work was to evaluate the distribution of imidazolinone-resistant (IMI-R) red rice (Oryza sativa) populations, the frequency of alleles conferring resistance to IMI, and the adoption of agronomic practices applied to red rice control, across growing seasons and production regions of the state of Rio Grande do Sul (RS), Brazil. In the experiment, 1,008 red rice populations were screened for resistance to IMI, 760 IMI-R red rice plants were genotyped for the acetolactate synthase (ALS) allel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…In Brazil, resistant weedy rice was detected 3 to 4 yr after adoption of the CL rice production system (Merotto et al 2016). A long-term study conducted between 2006 and 2012 found resistant weedy rice in 56% to 100% of the analyzed suspected populations (Kalsing et al 2019), indicating the high occurrence of IMI-resistant weedy rice in rice cultivation in southern Brazil. Gene flow was the primary origin of IMI-resistant weedy rice, but independent selection occurred in 1.1% of the weedy rice plants evaluated, a frequency similar to that in other weeds subject to herbicide selection pressures (Goulart et al 2012).…”
Section: Challenges For CL Rice Production In Brazilmentioning
confidence: 99%
See 1 more Smart Citation
“…In Brazil, resistant weedy rice was detected 3 to 4 yr after adoption of the CL rice production system (Merotto et al 2016). A long-term study conducted between 2006 and 2012 found resistant weedy rice in 56% to 100% of the analyzed suspected populations (Kalsing et al 2019), indicating the high occurrence of IMI-resistant weedy rice in rice cultivation in southern Brazil. Gene flow was the primary origin of IMI-resistant weedy rice, but independent selection occurred in 1.1% of the weedy rice plants evaluated, a frequency similar to that in other weeds subject to herbicide selection pressures (Goulart et al 2012).…”
Section: Challenges For CL Rice Production In Brazilmentioning
confidence: 99%
“…The continuous use of CL rice, the lack of diverse herbicide MOAs, and higher herbicide rates are factors that contribute to more frequent weed resistance to ALS-inhibiting herbicides in rice farms. In general, few growers adopt herbicide rotation to minimize the evolution and spread of weed resistance to herbicides (Kalsing et al 2019; Norsworthy et al 2013).…”
Section: Challenges For CL Rice Production In Brazilmentioning
confidence: 99%
“…In addition to this, an increase in the presence of red rice (Oryza sativa L.), especially in long rice-history systems, has also prompted the augmentation of the use of Clearfield technology [20]. Although a strong stewardship program existed, not all of the management recommendations have been followed in all situations, resulting in higher risks of selecting E. crus-galli biotypes resistant to imazapyr + imazapic (IMIS), in addition to resistant red rice [21,22]. It is an open secret that most farmers do not apply preventive measures unless they face the problem personally [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…The non-chemical control methods are usually laborious and expensive, and weedy rice is easily dispersed along with the seed of cultivated rice, also establishing a persistent seed bank (Chin, 2001). So, the management of this weed should be based on integrated practices (Watanabe, 2011), which include using high-purity certified seeds, previous preparation of the soil, rotation of production systems (Kalsing et al, 2019), a fast establishment of the ponding water depth (Avila et al, 2005), and application of herbicides in presowing (Noldin et al, 2002).…”
Section: Introductionmentioning
confidence: 99%